Transverse effects on the nasomaxillary complex one year after rapid maxillary expansion as the only intervention: A controlled study - Baratieri,Carolina da Luz (2014)
The aim of this study was to assess by means of cone-beam computed tomography (CBCT) scans the transverse effects on the nasomaxillary complex in patients submitted to rapid maxillary expansion (RME) using Haas expander in comparison to untreated individuals. This prospective controlled clinical study assessed 30 subjects (18 boys and 12 girls) with mixed dentition and during pubertal growth. The treated group was submitted to RME with Haas expander, retention for six months and a six-month follow-up after removal. The control group matched the treated group in terms of age and sex distribution. CBCT scans were taken at treatment onset and one year after the expander was activated. Maxillary first molars (U6) width, right and left U6 angulation, maxillary alveolar width, maxillary basal width, palatal alveolar width, palatal base width, right and left alveolar angulation, palatal area, nasal base width, nasal cavity width and inferior nasal cavity area on the posterior, middle and anterior coronal slices were measured with Dolphin Imaging Software(r) 11.5, except for the first two variables which were performed only on the posterior slice. All transverse dimensions increased significantly (P < 0.05) in the treated group in comparison to the control, except for alveolar angulation and inferior nasal cavity area (P > 0.05). Results suggest that increase of molar, maxillary, palatal and nasal transverse dimensions was stable in comparison to the control group one year after treatment with RME.